IMPLIKASI KEBERADAAN YOGA ANANDA MARGA UNIT KARANGASEM TERHADAP MASYARAKAT KARANGASEM - I Wayan Lali Yogantara (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Yoga Ananda Marga Unit Karangasem is located on Amlapura City. However, the existence of some people in the city of Amlapura has not been known until now. The study was directed to get clarity about the implications of the existence of the Yoga Ananda Marga Unit Karangasem on the Karangasem community. Data is obtained by observation, interview, documentation, and literature study methods. The results showed that the implications of the existence of the Yoga Ananda Marga Unit in Karangasem include increasing the spiritual awareness of the community by conducting yoga activities with the community both conducted at the Ashram Yoga Ananda Marga Unit Karangasem and outside the ashram, especially yoga asanas, while for fasting camp, akhanda kiirtan and prabhat samgiit exercises were carried out at the Ashram Yoga Ananda Marga Unit in Karangasem; and the implications for social behavior were reflected in the form of social assistance in the form of delivery of groceries, cash assistance, free treatment, and home surgery